Violation of Human Rights in The Perspective of The Sociology of Law Judiciary in Indonesia - Jamillah Jamillah (International Asia Of Law and Money Laundering (IAML), 2022)
Protection of Human Rights (HAM) is one of the characteristics of the rule of law. Violation of the right to life is a serious Human Rights violation that is qualified as a crime against humanity and a crime of genocide. Indonesia has enacted UU No.26 Tahun 2000 on Human Rights Courts as the basis for establishing a retroactive Ad Hoc Human Rights Court. Settlement of past gross human rights violations through the courts has been conducted in the 1999 East Timor case and the Tanjung Priok case in 1984. Both cases were terminated "free" at the Cassation and Reconsideration. From the judicial sociology review, both Judges' decisions are in fact extraction of interpretations of legal norms, moral values and social interests that live in society and become the nation's view. The sociological legal perspective provides the view that the judicial settlement has not been able to provide a sense of justice and beneficiary as a legal objective, therefore a non-judicial resolution is required for other cases of gross human rights abuses, as adopted by the Public Prosecution Service together with other government elements and Komnas HAM.